COMMUNITY PATTERNS OF GROUND-DWELLING INSECTS ACROSS A CANOPY COVER GRADIENT IN A TROPICAL CAMPUS LANDSCAPE - Astihawa Indah Setiani; Muhammad Ridwan; Firnandez Ngariswara Vidsia Sadana; Moh Reza Sese; Puji Rianti; Windra Priawandiputra; Tri Atmowidi (BRIN Publishing (Penerbit BRIN), 2025)
Canopy cover influences soil surface microhabitats and may affect the structure of ground-dwellinginsect communities, yet evidence from plantation-dominated landscapes remains limited. This studyexamined ground-dwelling insect community patterns in relation to canopy cover and selectedenvironmental variables across three sites within the IPB Dramaga Campus: Arboretum (83.91%), OilPalm (71.91%), and Cikabayan (0.00%). Canopy cover was quantified using hemisphericalphotography, and insects were sampled using pitfall traps over five consecutive days in July 2024.Community composition was analyzed using PERMANOVA, which indicated no significant differencesamong sites (R = 0.861, p = 0.067). Non-metric Multidimensional Scaling (NMDS) was thereforeapplied as an exploratory ordination to visualize community patterns and interpreted descriptively giventhe limited sample size. A total of 1,711 individuals were recorded, with overall abundance highest inthe Oil Palm site, followed by Cikabayan and the Arboretum. The Arboretum exhibited lower totalabundance but higher evenness and Shannon diversity, whereas the Oil Palm site showed highabundance with lower diversity and evenness, reflecting dominance by a few families. Cikabayandisplayed intermediate diversity patterns. Differences among sites were primarily reflected in relativeabundance and dominance rather than clear taxonomic turnover. Overall, canopy structure wasassociated with variation in ground-dwelling insect assemblages, although statistically significantcompositional differences were not detected, highlighting the need for broader spatial and temporalsampling before firm management recommendations can be made.